Quantifying the divide: a comparison of ICT usage of schools in Metro Manila and IEA-surveyed countries - Rodrigo, Ma. Mercedes T (Archīum Ateneo, 2005)
The researcher quantified the digital divide that existed between schools in Metro Manila, Philippines and schools in countries surveyed by the International Association for the Evaluation of Educational Achievement. The researcher determined that unlike students in other countries, students in Metro Manila schools had limited access to computers, software, and the Internet. This implies that Metro Manila students are among the digital poor, with fewer opportunities to access, process, and contribute to digital content.